Biomimetic honeycomb Zn anode enabled multi-field regulation toward highly stable flexible Zn-ion batteries - Liu, Huaizhi (2023)
Flexible Zn-ion batteries (ZIBs) emerge as a promising entrant for flexible and safe energy systems in the post-Li era, while the instability of Zn anode including inferior flexibility, uncontrollable plating, and dendrite growth remains a challenge. Naturally inspired, a topology-optimized biomimetic honeycomb Zn (BH-Zn) anode through mechanical-electrochemical processing is demonstrated. Numerical simulations and experimental observations reveal the BH-Zn engenders smooth current–stress–thermal field distributions, concurrently realizing the multi-field regulation effect and boosted stability. After in situ alloying, the BH-Zn enables half-diminished voltage polarization, superior electrochemical stability of 2000 h cycling, and thermal stability even at 30 mA cm−2. Moreover, the assembled ZIBs manifest over 20 times enhanced capacity retention and are integrated as a self-powered wearable system for real-time health monitoring. This strategy can be extended to customizable metal anodes and promises to be applied in stable flexible batteries.